Diffusion kinetics investigations of Nano Ag-doped holographic polymer dispersed liquid crystal gratings. Issue 12 (26th September 2019) - Liu, Yourong; Zheng, Jihong; Shen, Tong; Wang, Kangni; Zhuang, Songlin
ABSTRACT: In this paper, we use multicomponent mutual diffusion method to derive a one-dimensional non-local diffusion dynamic model to describe the diffusion kinetics of a dynamic holographic polymer dispersed liquid crystal grating (H-PDLC) doped with nano-silver. The physical mechanism of diffusion between monomer and liquid crystal, monomer and nano-silver particles is analysed using this model. Using coupled-wave theory, the H-PDLC's diffraction efficiency curve with the expose time are simulated due to the vivid changing of effective refractive index modulation caused by the movement of concentration of each component with the expose time. Correspondingly, in the experiment, the diffraction efficiency of the grating is measured in real time, which shows the improvement for the holographic properties because of nano-silver doped H-PDLC. The simulation results have a good agreement with experimental data by fitting the corresponding parameters of the model. In addition, through comparing with simulation and experimental results with doping different concentrations of nano-silver particles, the recipe and diffraction characteristics of H-PDLC grating can be improved. Thus, the diffusion Kinetics model can be used to optimise the phase separation of the PDLC grating, and finally to improve the opto-electrical properties of H-PDLC gratings. GRAPHICAL ABSTRACT: